Emerging Design in Cities: Use of Urban Space and the Phenomenon of Street Markets - Sosa, Liliana Beatríz (UNIVERSIDAD DE SONORA, 2022)
Street markets represent a social phenomenon that triggers the emergence of identities, configuration and use of spaces from the interaction of people, objects and their environment. The present document deals with the emergence of urban design and the self-production of public space as a consequence of the social organization that sustains street markets. In the first instance, a theoretical foundation of the perspective of complex systems used to address the phenomenon is established; then street markets are explored from different perspectives: the activities, motives and customs of the people who produce them and interact in them, as well as an analysis, in case studies, of their structure and dynamics of the use of streets and built spaces, in order to reflect on its emergence, benefits and potential for use in urban systems. The nature of this study is qualitative, exploratory and descriptive, aimed at establishing general guidelines for intervention with design in street markets in order to take advantage of them as systems that improve the experience of inhabiting the city.